(untitled) (Relevant Tomorrow / Aktualu rytoj, 2023)
Today’s World ORT, or Organization for Rehabilitation through Training is the world’s largest Jewish vocational education organization, helping more than just Jews to find a profession. The article reconstructs the circumstances of the ORT’s foundation and its development until it became a world organization in 1921, and highlights the distinctiveness of the ORT Vilna Technicum (1921–1940). The policy of liberation pursued by Tsar Alexander II of Russia, and in particular the decree of 1865 allowing skilled craftsmen to settle all over Russia outside the confines of the Pale of Settlement, led to the establishment of the organization in St Petersburg in 1880. The purpose of the ORT was to help Jewish society adapt to the economic conditions of the new times by moving towards manufacturing work. From 1921 until 1940, the ORT Vilna Technicum was the most prestigious Jewish vocational school in Poland and in the entire ORT system. The word “technicum” in the school’s name, adopted from the German education system, was new in Poland at that time. In the course of the adjustment to the Polish education system, the name was changed a few times: from 1932, this Jewish educational institution was called a private technicum, and from 1938, a technical lyceum. Graduates of this school were given the degree of technician (assistant engineer) and were able to find immediate employment or to continue their studies at foreign technical colleges and universities.